2011
DOI: 10.5021/ad.2011.23.s1.s57
|View full text |Cite
|
Sign up to set email alerts
|

The Three Dimensional Conformal Radiotherapy for Hyperkeratotic Plantar Mycosis Fungoides

Abstract: The localized early-stage of Mycosis fungoides (MF) (stage IA-IIA) is usually treated with topical agents, such as nitrogen mustard, steroids, and phototherapy (UVB/PUVA) as first line therapy; response to these initial treatments is usually good. However, hyperkeratotic plantar lesions are clinically rare and have decreased responsiveness to topical agents. For such cases, physicians may consider local radiotherapy. Here, a case of an 18-year-old Korean woman who was treated with three-dimensional conformal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…4,5 Traditional doses range from 2000 to 4000 cGy compared with the 800-cGy dosing given in 2 fractions of 400 cGy administered in the present study. Lee et al 11 reported a single case of the use of 3-dimensional conformal radiotherapy, a technique using a photon beam that penetrates to a greater depth than EBT, for hyperkeratotic plantar MF, using 4000 cGy in normal fractionation with complete lesion clearance. Chan et al 12 reviewed 10 cases of unilesional or oligolesional CTCL and demonstrated that, in all 10 patients, the use of 3000 to 3600 cGy showed a disease-free survival of 70% at a mean follow-up time of 40 months; however, significant toxic effects were noted.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Traditional doses range from 2000 to 4000 cGy compared with the 800-cGy dosing given in 2 fractions of 400 cGy administered in the present study. Lee et al 11 reported a single case of the use of 3-dimensional conformal radiotherapy, a technique using a photon beam that penetrates to a greater depth than EBT, for hyperkeratotic plantar MF, using 4000 cGy in normal fractionation with complete lesion clearance. Chan et al 12 reviewed 10 cases of unilesional or oligolesional CTCL and demonstrated that, in all 10 patients, the use of 3000 to 3600 cGy showed a disease-free survival of 70% at a mean follow-up time of 40 months; however, significant toxic effects were noted.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement limited to or primarily affecting the palmoplantar surfaces was reported in 0.6% of MF cases, a variant termed MF palmaris et plantaris. Since the publication of this review in 1995, cases of acquired PPK as the first or only sign of MF have been infrequently reported and include that of an 18‐year old woman …”
Section: Discussionmentioning
confidence: 99%
“…Histologic findings considered as PA by Lee et al1 favor more PPA, judging from adjacent prominent spongiosis, and predominance of nonlymphoid cells, showing presence of histiocyte, Langerhans cell, and stellate keratinocyte without atypical features. Additional immunohistochemical study will be also useful in the differential diagnosis, using CD1a, CD3, CD4, CD68, and high molecular cytokeratin5.…”
mentioning
confidence: 95%
“…We read with great interest the article by Lee et al 1 entitled "The three dimensional conformal radiotherapy for hyperkeratotic plantar mycosis fungoides" 1 . We agree with the effectiveness of three-dimensional conformal radiotherapy for hyperkeratotic plantar mycosis fungoides (MF) and appreciate the educational figures.…”
mentioning
confidence: 99%
See 1 more Smart Citation